Influence of dietary ingredients on pork fat quality - Benz, Justin M. (Kansas State University, 2008)
Five-hundred and four barrows and gilts were used in four experiments to determine the influence of dietary ingredients on fat quality. Experiment 1 evaluated feeding duration of choice white grease (CWG) and soybean oil. Increasing feeding duration of pigs fed CWG or soybean oil increased (quadratic, P < 0.01) iodine value (IV) in jowl fat and backfat. Pigs fed soybean oil had increased (P < 0.01) IV in jowl and backfat compared with pigs fed CWG. In Exp. 2 dried distillers grains with solubles (DDGS), extruded expelled soybean meal (EESM), and CWG were used to evaluate diets with common iodine value product (IVP) from ingredients varying in unsaturated fat level and concentration. Pigs fed either diet with DDGS had increased (P = 0.02) backfat and jowl fat IV, compared with all other treatments. Pigs fed EESM had increased (P = 0.04) backfat and jowl fat IV compared with the control, low CWG, and high CWG. Pigs fed low CWG and high CWG had increased (P = 0.04) jowl fat IV compared to the control. Increasing dietary fat increased carcass fat IV, with unsaturated fats from DDGS and EESM having a greater affect than more saturated fats, such as CWG, even when formulated to the same IVP. Experiment 3 evaluated the effects of increasing CWG in corn- and sorghum-based diets on fat quality. There was a grain source X fat level interaction (P = 0.04) for IV in both backfat and jowl fat. Adding CWG increased IV in backfat and jowl fat for pigs fed corn- and sorghum-based diets; however, the greatest increase was between 0 and 2.5% CWG in sorghum-based diets and between 2.5 and 5% CWG in corn-based diets. Despite this interaction, pigs fed corn-based diets had increased (P < 0.01) backfat and jowl fat IV compared with pigs fed sorghum-based diets. Increasing CWG increased (linear, P < 0.01) IV in backfat and jowl fat. Experiment 4 examined the effects of DDGS on fat quality. Backfat, jowl fat, and belly fat IV increased (linear, P = 0.02) with increasing DDGS in both the pigs marketed on d 57 and 78.
Keywords: pigs; fat quality; iodine value; Agriculture, Animal Culture and Nutrition (0475)